A review and comparison of surface incident shortwave radiation from multiple data sources: satellite retrievals, reanalysis data and GCM simulations. Issue 1 (31st December 2023) - Yang, Shuyue; Zhang, Xiaotong; Guan, Shikang; Zhao, Wenbo; Duan, Yanjun; Yao, Yunjun; Jia, Kun; Jiang, Bo
ABSTRACT: Surface incident shortwave radiation ( Rs ) can promote the circulation of substance and energy, and the accuracy of its estimation is of great significance for climate studies. The Rs can be acquired from satellite retrievals, reanalysis predictions and general circulation model (GCM) simulations. Although Rs estimates have been evaluated and compared in previous studies, most of them focus on evaluating the Rs estimates over specific regions using ground measurements from limited stations. Therefore, it is essential to comprehensively validate Rs estimates from multiple data sources. In this study, ground measurements of 690 stations from BSRN, GEBA, CMA, GC-NET and buoys were employed to validate the Rs estimates from seven representative products (GLASS, GEWEX-SRB, CERES-EBAF, ERA5, MERRA2, CFSR and CMIP6). The validation results indicated that the selected products overestimated Rs globally, with biases ranged from 0.48 to 21.27 W/m 2 . The satellite retrievals showed relatively better accuracy among seven datasets compared to ground measurements at the selected stations. Moreover, the selected seven products were all in poor accuracy at high-latitude regions with RMSEs greater than 50 W/m 2 . The long-term variation trends were also analyzed in this study.